Mengidentifikasi Kemampuan Berpikir Kritis dan Representasi Multidimensi Siswa dalam Materi Larutan Buffer Menggunakan Alat Elektronik Melalui Jotform - Tissa Indah; Susilawati Susilawati; Dedi Futra (Jurnal Tadris Kimiya, 2026)
Critical thinking and multiple representation skills are essential competencies for meaningful chemistry learning, particularly when students are required to connect macroscopic phenomena, microscopic particle behavior, and symbolic chemical representations. However, evidence regarding students’ achievement in these skills remains limited, especially in the context of buffer solution learning. This study aimed to profile secondary students’ critical thinking and multiple representation skills using a previously validated web-based assessment instrument. A quantitative descriptive design was employed involving 74 eleventh-grade students from three secondary schools in Riau Province, Indonesia. Data were collected through an electronic assessment administered via Jotform and analyzed using descriptive statistics. The assessment measured five critical thinking dimensions (interpretation, analysis, inference, evaluation, and explanation) and three representation levels (macroscopic, microscopic, and symbolic). The findings revealed that students’ critical thinking skills ranged from moderate to good levels across schools, with explanation emerging as the strongest dimension. In terms of multiple representations, students demonstrated better performance in symbolic and macroscopic representations than in microscopic representations. Students from School A achieved the highest scores in both critical thinking and multiple representation skills, whereas students from School B showed the lowest performance. The results indicate that students continue to experience difficulties in interpreting microscopic chemical phenomena despite demonstrating satisfactory understanding of symbolic and macroscopic aspects. These findings provide valuable insights for chemistry educators in designing instructional and assessment strategies that better support the development of higher-order thinking and representational competence in chemistry learning.